Inhibition in radiation mediated cellular toxicity by minimizing free radical flux: one of the possible mechanisms of biological protection against lethal ionizing radiation by a sub- fraction of Podophyllum hexandrum - Gupta, M. L.; Gupta, V.; Shukla, S. K.; Verma, S.; Sankhwar, S.; Dutta, A.; Suri, K. A. (Cellular and Molecular Biology, 2010)
The study has focused on exploring the mechanism of action of Podophyllum hexandrum sub-fraction (G-001M) exhibiting >90% protection in lethally irradiated mice. Currently, G-001M was assessed for antioxidant characteristics by evaluating DPPH, superoxide and hydrogen peroxide radical formation, anti-lipid per oxidation, metal chelation and total flavonoid content. To affirm cytoprotective efficacy of G-001M, plasmid DNA protection, blood WBC counts, marker for lipid peroxidation (MDA) and antioxidant status (GSH) in mice splenocytes and thymocytes were studied. G-001M, having high amount of total phenolic contents (200±10mg, w/w), exhibited dose dependent inhibition in DPPH and superoxide radical formation. Hydrogen peroxide radical scavenging was higher than standards. With pre-treatment of G-001M, plasmid DNA was also maximally restored to supercoiled form. Radiation modulated MDA and GSH values in splenocytes and thymocytes of mice altered significantly after 24 hrs and at later intervals, values were close to the controls. Radiation mediated losses in WBC counts were significantly regained (p<0.001) in G-001M pre-treated irradiated mice. The above findings explicitly conveyed that G-001M has successfully minimized radiation inflicted free radicals generation and their multiplication. This activity of G-001M could be undoubtedly among one of the major modes of action in extending whole body survival in lethally irradiated mice.